The Sustainability of Saltworks Integration in Pati Regency, Central Java - Sriwati Sriwati; Aziz Nur Bambang; Johannes Hutabarat; Haeruddin Daeng Mile; Tri Winarni Agustini (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight ResearchThe rainfall intensity can affect the phenomenon of salt farmers, so farmers must have adaptation strategiesSalt Business Group (SBG) is a group of people who have saltworks activities with a minimum number of administratorsThe profit sharing system between the owners and the farmers (called pemadak) is an important factor affecting the income of salt farmersThe function of the kite diagram is to position the value of the sustainability status from the ecological, technological, economic, social and institutional (etesi) aspectsAbstractSaltworks integration is one of the government's efforts as a breakthrough in saltworks technology innovation. Saltworks integration in Pati Regency has been conducted for 4 (four) years starting from 2017 to 2020. The aim of this research was to analyze the sustainability of saltworks integration in terms of ecological, technological, economic, social, and institutional (ETESI) aspects. The research was conducted for 9 (nine) months from March to November 2020. The research locations for saltworks integration were in Raci Village - Batangan Subdistrict, Genengmulyo Village - Juwana Subdistrict, Tluwuk Village - Wedarijaksa Subdistrict, and Kertomulyo Village - Trangkil Subdistrict. Sustainability analysis was performed using Rapfish method. Through the R software, the anchor was created automatically so that users only need to input data through Microsoft Excel, then the Rapfish analysis was carried out automatically by the R software. The results of the sustainability index analysis of saltworks integration in the ecological aspects of Raci Village, Batangan Subdistrict showed a sustainable index value. Genengmulyo Village - Juwana Subdistrict, Tluwuk Village - Wedarijaksa Subdistrict, and Kertomulyo Village - Trangkil Subdistrict had an opportunity of attaining sufficiently sustainable status by considering indicators that affect its sustainability. Technological, economic, social and institutional aspects in all villages, where saltworks integration was located, showed a sufficiently sustainable status.